"Candidatus Phytoplasma aurantifolia" increased the fitness of Hishimonus phycitis; the vector of lime witches' broom disease. (April 2021) - Hemmati, Chamran; Nikooei, Mehrnoosh; Al-Sadi, Abdullah M.
Abstract: Hishimonus phycitis is one of the main insect vectors of phytoplasmas, in particular of ' Candidatus Phytoplasma aurantifolia'-related strains associated with witches' broom disease in many crops. A study was conducted to investigate the relationship between H. phycitis infection by phytoplasmas and some of its biological parameters. H. phycitis harboring phytoplasmas resulted in more fecundity (higher number of offspring produced) and higher nymph developmental rate compared to uninfected insects. The finite rate of population increase ( λ ) and net reproductive rate ( R 0 ) were higher in phytoplasma-infected H. phycitis indicating that the overall fitness of the infected population was improved. The survival of phytoplasma-infected female was lower compared with infected male, which suggest that they may be a fitness trade-off in response to phytoplasma infection. A beneficial effect of a plant pathogen on vector fitness may indicate that the pathogen developed a relationship with the insect first, then moving to the plant secondarily. Taken together, our findings suggest that elimination of the infected trees (as a source of inoculum) should be a relevant part of the lime witches' broom disease management. Highlights: Hishimonus phycitis is the major vector of the phytoplasma associated with lime witches' broom disease. H. phycitis harboring phytoplasma had more fecundity and produced more offspring compared to uninfected counterparts. Fitness parameters increased in individuals harboring phytoplasma. The elimination of the infected trees (as a source of inoculum) is a relevant part of the WBDL management.